Risk Factors for Preterm Birth among HIV-Infected Tanzanian Women: A Prospective Study - Rachel M. Zack; Jenna Golan; Said Aboud; Gernard Msamanga; Donna Spiegelman; Wafaie Fawzi (Obstetrics and Gynecology International)
Premature delivery, a significant cause of child mortality and morbidity worldwide, is particularly prevalent in the developing world. As HIV is highly prevalent in much of sub-Saharan Africa, it is important to determine risk factors for prematurity among HIV-positive pregnancies. The aims of this study were to identify risk factors of preterm (<37 weeks) and very preterm (<34 weeks) birth among a cohort of 927 HIV positive women living in Dar es Salaam, Tanzania, who enrolled in the Tanzania Vitamin and HIV Infection Trial between 1995 and 1997. Multivariable relative risk regression models were used to determine the association of potential maternal risk factors with premature and very premature delivery. High rates of preterm (24%) and very preterm birth (9%) were found. Risk factors (adjusted RR (95% CI)) for preterm birth were mother <20 years (1.46 (1.10, 1.95)), maternal illiteracy (1.54 (1.10, 2.16)), malaria (1.42 (1.11, 1.81)), Entamoeba coli (1.49 (1.04, 2.15)), no or low pregnancy weight gain, and HIV disease stage ≥2 (1.41 (1.12, 1.50)). Interventions to reduce pregnancies in women under 20, prevent and treat malaria, reduce Entamoeba coli infection, and promote weight gain in pregnant women may have a protective effect on prematurity.